ANALISIS POTENSI PAJAK DAN RETRIBUSI DAERAH KABUPATEN SUBANG - Zaenal Hirawan (Universitas Sultan Ageng Tirtayasa, 2016)
The study aims to see how the contribution of taxes and retribusi on revenue(PAD) Subang Regency 2010-2014. The method used to analyze the method with aqualitative approach, with the consideration that the resulting research will dig deeper.The results showed that the contribution of the 2010-2014 tax is very large compared tothe contribution charges and revenue from other areas. In 2011 had a highercontribution to regional revenue amounted to 33.8% so that development financingwould be better. To levy contributions to the regional revenue of years 2010-2014 stillflukatuatif. So that taxes are still the main attraction in the process of financing thedevelopment of a particular area of Subang regency.